2011
DOI: 10.1080/03088839.2011.556677
|View full text |Cite
|
Sign up to set email alerts
|

To partner or to acquire? A longitudinal study of alliances in the shipping industry

Abstract: How do firms in the liner shipping industry choose between partnerships and acquisitions? In this longitudinal empirical study, we examine dyadic partnerships and acquisitions that took place in the liner shipping industry from 1994 to 2006. We identify and test specific factors that influence liner shipping firms in their strategic choice between partnerships and acquisitions. Using Cox regressions for our analyses, we find that two factors, the extent of redundant resources and the intensity of competition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…In this regard, as discussed by some scholars (Midoro and Pitto, 2000;Sjostrom, 2010), cooperative agreements are strongly driven by market factors. In particular, in highly competitive geographic markets, shipping lines are expected to experience more intense forms of cooperation, in order to avoid destabilising effects of competition (Das, 2011). Therefore:…”
Section: 'Leveraging' the Operated Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, as discussed by some scholars (Midoro and Pitto, 2000;Sjostrom, 2010), cooperative agreements are strongly driven by market factors. In particular, in highly competitive geographic markets, shipping lines are expected to experience more intense forms of cooperation, in order to avoid destabilising effects of competition (Das, 2011). Therefore:…”
Section: 'Leveraging' the Operated Capacitymentioning
confidence: 99%
“…Scholars (Ferrari et al, 2008;Parola and Veenstra, 2008;Ducruet et al, 2010) have studied the geographic scope of ocean carrier services, without expanding on the relevance of consortia and alliances within various market dynamics. In this regard, the fierce competition that is now taking place in the key geographic markets and the current unstable macroeconomic trend (Das, 2011) have discouraged shipping lines from pursuing lose-lose competitive games. Therefore, we may assume that: H2 The bigger the geographic market size (trade lane), the higher is the propensity to cooperate.…”
Section: Propensity To Cooperatementioning
confidence: 99%
See 1 more Smart Citation
“…Wen (2012) also observed that collaborative arrangements served to boost logistics capability and competitive advantage of shipping lines. Nonetheless, container shipping alliances were found to be inherently unstable having seen structural changes over the years (Das, 2011). Rau and Spinler (2017) observed that the intensity of competition, cost of complexity of the alliance and volatility in freight rate led to alliance instability.…”
Section: Introductionmentioning
confidence: 99%
“…Under such arrangement, sensitive information, such as trade secrets, is not shared because the allied carriers remain separate corporate entities that compete against one another (Das, 2011).…”
Section: Ocean Shipping Alliancementioning
confidence: 99%